Identification of a new export signal that targets early subunits to the flagellar type III secretion export machinery - Owain J. Bryant; Gillian M. Fraser (mBio, 2024)
ABSTRACT Type III secretion systems (T3SSs) are essential for motility and virulence in many bacterial pathogens. Proteins destined for the flagellar T3SS contain at least two export signals in their N-terminal D0 domain. Here, we describe a third carboxy (C)-terminal signal in early flagellar subunits that facilitates subunit targeting to the export machinery. Mutational analysis identified critical residues within the flagellar hook subunit C-terminal export signal. The flagellar ATPase and cytoplasmic ring components were not required for this targeting, indicating that core export machinery components facilitate substrate targeting via the C-terminal export signal. More broadly, these results demonstrate that multiple distinct export signals within type III secretion substrates facilitate distinct export events at the T3SS export machinery. Our data establish key events in the export mechanism of type III secretion systems: targeting of subunits to and their sequential interactions with key components of the export machinery.IMPORTANCEMany bacterial pathogens utilize T3SS to inject virulence proteins (effectors) into host cells or to assemble flagella on the bacterial cell surface. Bacterial flagella present a paradigm for how cells build and operate complex cell-surface “nanomachines.” Efficient subunit targeting from the bacterial cytosol to type III secretion systems is essential for rapid assembly and secretion by T3SSs. Subunits are thought to dock at the export machinery before being unfolded and translocated into the export channel. However, little is known about how subunits dock at the export machinery and the events that occur post docking. Here, we identified a new export signal within the C-termini of subunits that is essential for targeting of subunits to the type III export machinery. We show that this new export signal and previously identified export signals are recognized separately and sequentially, revealing a pathway for subunit transit through the type III export machinery in which sequential recognition events carry out different roles at major steps in the export pathway.